THE EFFECT OF FINANCIAL LITERATURE AND FINANCIAL TECHNOLOGY ON COMMUNITY FINANCIAL INCLUSION (CASE STUDY ON ADOLESCENT IN CITY OF TEBING TINGGI, NORTH SUMATERA) - Radiman, Radiman; Wahyuni, Sri Fitri; Novika, Indah Ayu (Journal of International Conference Proceedings, 2022)
ABSTRACTThis study aims to determine and analyze the Effect of Financial Literacy and Financial Technology on Public Financial Inclusion (Case Study on Teenagers in Tebing Tinggi City, North Sumatra). This research method uses a quantitative approach and uses associative research with questionnaire data collection techniques. The population in this study amounted to 27,837 people in Tebing Tinggi city teenagers and this study used incidental sampling technique, taking a sample of 100 respondents. The data analysis technique in this study used the classical assumption test, multiple linear regression test, research hypothesis testing (t test and F test), and the coefficient of determination. Based on the results of this study, financial literacy has a significant influence on community financial inclusion in Tebing Tinggi city adolescents, financial technology has a significant influence on community financial inclusion in Tebing Tinggi city adolescents, financial literacy and financial technology affect community financial inclusion in Tebing Tinggi city adolescents.Key Words : Financial Literacy, Financial Technology, Financial InclusionJEL Classification:B26, C58, E26